Conservative versus Surgical Management of Appendicitis During Pregnancy - Edwardes, Chantal; Sud, Vikas (Journal of the Nuffield Department of Surgical Sciences, 2022)
Acute appendicitis is the most common non-obstetric surgical emergency during pregnancy. This report presents a case of conservative management of appendicitis during pregnancy. The aim is to discuss the role of conservative treatment for a condition that is routinely treated surgically. This is important because research on the management of appendicitis during pregnancy is limited compared to the general population. Conservative management can be a safe option for uncomplicated appendicitis. However, the increased risk of appendix perforation in pregnancy and implications for foetal health commonly make surgery a more attractive option. This risk is a key driver for higher rates of negative appendectomies during pregnancy. The COVID-19 pandemic provides a unique opportunity to remedy the paucity of research of appendicitis during pregnancy. This is because conservative management was heavily utilised at the start of the pandemic. Therefore, following up pregnant patients in this cohort will provide a valuable insight into the risks and benefits of conservative versus surgical management.